Question
upstudy study bank question image url

6. \( (90 \div 6) \times\{-2+[3 \times(5+1)-(8-4)+3]\} \) 7. \( [7 \times 10-11] \times(5 \times 2)+[(15 \div 3) \times 8] \) 8. \( [(3 \div 3) \times 2-2+5 \div(4+1)]+(6 \times 4) \)

Ask by Schwartz Grant. in Colombia
Feb 25,2025

Upstudy AI Solution

Tutor-Verified Answer

Answer

6. 225 7. 630 8. 25

Solution

Procedimiento y resultados: 6. (90 ÷ 6) × { -2 + [3 × (5 + 1) – (8 – 4) + 3] } - Primero, 90 ÷ 6 = 15. - Dentro de las llaves: ▫ Se calcula (5 + 1) = 6, luego 3 × 6 = 18. ▫ Se calcula (8 – 4) = 4. ▫ Se evalúa la expresión en corchetes: 18 – 4 + 3 = 17. ▫ Se suma: –2 + 17 = 15. - Finalmente: 15 × 15 = 225. 7. [7 × 10 – 11] × (5 × 2) + [(15 ÷ 3) × 8] - Primero, en los corchetes: 7 × 10 – 11 = 70 – 11 = 59. - Luego, (5 × 2) = 10. - En la última parte: 15 ÷ 3 = 5, y 5 × 8 = 40. - Se multiplica: 59 × 10 = 590, y sumando: 590 + 40 = 630. 8. [(3 ÷ 3) × 2 – 2 + 5 ÷ (4 + 1)] + (6 × 4) - Primero, (3 ÷ 3) = 1, y 1 × 2 = 2. - Se suma restando: 2 – 2 = 0. - Se calcula (4 + 1) = 5, luego 5 ÷ 5 = 1. - Sumando dentro de los corchetes: 0 + 1 = 1. - Finalmente, (6 × 4) = 24, y 1 + 24 = 25. Resultados finales: 6. 225 7. 630 8. 25

Answered by UpStudy AI and reviewed by a Professional Tutor

error msg
Explain
Simplify this solution

Extra Insights

To solve the first expression \( (90 \div 6) \times\{-2+[3 \times(5+1)-(8-4)+3]\} \), first compute \( 90 \div 6 = 15 \). Next, simplify the inner expression: \( 5 + 1 = 6 \), so \( 3 \times 6 = 18 \). Then calculate \( 8 - 4 = 4 \), leading to \( -2 + 18 - 4 + 3 = 15 \). Now multiply, \( 15 \times 15 = 225 \). For the second expression \( [7 \times 10-11] \times(5 \times 2)+[(15 \div 3) \times 8] \), begin with the brackets: \( 7 \times 10 = 70 \) and \( 70 - 11 = 59 \). Then \( 5 \times 2 = 10 \) and, multiplying these gives \( 59 \times 10 = 590 \). For the other part, \( 15 \div 3 = 5 \) and then \( 5 \times 8 = 40 \). Finally, adding these results gives \( 590 + 40 = 630 \). Lastly, for \( [(3 \div 3) \times 2-2+5 \div(4+1)]+(6 \times 4) \), simplify the brackets: \( 3 \div 3 = 1 \), hence \( 1 \times 2 = 2 \). The full expression reads \( 2 - 2 + 5 \div 5 = 2 - 2 + 1 = 1 \). Now calculate \( 6 \times 4 = 24 \), leading to a final sum of \( 1 + 24 = 25 \). So the final answers for the expressions are: 6. \( 225 \) 7. \( 630 \) 8. \( 25 \)

Related Questions

Latest Arithmetic Questions

Try Premium now!
Try Premium and ask Thoth AI unlimited math questions now!
Maybe later Go Premium
Study can be a real struggle
Why not UpStudy it?
Select your plan below
Premium

You can enjoy

Start now
  • Step-by-step explanations
  • 24/7 expert live tutors
  • Unlimited number of questions
  • No interruptions
  • Full access to Answer and Solution
  • Full Access to PDF Chat, UpStudy Chat, Browsing Chat
Basic

Totally free but limited

  • Limited Solution
Welcome to UpStudy!
Please sign in to continue the Thoth AI Chat journey
Continue with Email
Or continue with
By clicking “Sign in”, you agree to our Terms of Use & Privacy Policy